Facilitators to support the implementation of injury prevention training in youth handball: A concept mapping approach - Ageberg, E.; Bunke, S.; Lucander, K.; Nilsen, P.; Donaldson, A. (Scandinavian Journal of Medicine & Science in Sports, 2019)
There is a need for research to identify effective implementation strategies for injury prevention training within real-world community sports. The aim of this ecological participatory study was to identify facilitators, among stakeholders at multiple levels, that could help injury prevention training become part of regular training routines in youth team handball. Concept mapping, a mixed-method approach for qualitative data collection and quantitative data analysis, was used. Stakeholders (n = 196) of two community team handball clubs (29% players, 13% coaches, 38% caregivers, 11% club, district and national handball administrators, 9% unknown) participated in a brainstorming process. After the research team synthesized the 235 generated statements, 50 stakeholders (34% players, 22% coaches, 24% caregivers, 20% administrators) sorted 89 unique facilitator statements into clusters and rated them for importance and feasibility. Multidimensional scaling and hierarchical cluster analysis yielded five clusters (stress value 0.231): "Understanding and applying knowledge," "Education, knowledge, and consistency," "Set-up and exercises," "Inspiration, motivation, and routines," and "Club policy and expert collaboration." The cluster "Understanding and applying knowledge" had the highest mean importance (3.17 out of 4) and feasibility (2.93) ratings. The 32 statements rated as both highly important and feasible (Go-zone) indicate action is required at the individual (end-users) and organizational (policymakers) levels to implement injury prevention training. Results suggest that developing evidence-based context-specific injury prevention training, incorporating physiological, biomechanical and psychological components, and an associated context-specific implementation plan in partnership with all stakeholders should be a high priority to facilitate the implementation of injury prevention training in youth team handball.